Assessment of orthophoto generated from UAV images / Suaibah Ibrahim - Ibrahim, Suaibah (2020)
Unmanned Aerial Vehicle (UAV) has succeeded in attaining a position in the aerial image survey as a cheaper and more effective for 3-dimension-modelling compared to traditional photogrammetry and Light Detection and Ranging (LIDAR). Besides that, the utilization of UAV photogrammetry software is important in giving he highest accuracy for orthophoto production. This research will compare two different analysis on orthophoto. The project aims to assess the accuracy of plane coordinate on a orthophoto generated from aerial images. The ground control points (GCP) was carried out during the field survey observation and later the UAV images were processed by using the Agisoft PhotoScan software. The processing phases involved were photo alignment, geo-referencing, dense points cloud and mesh, texture model, Digital Elevation Model (DEM) and orthophoto with GCP distribution. The assessment on the accuracy of the software was based on both qualitative and quantitative analysis. The qualitative analysis includes points and distance measurement that used the RMSE method for accuracy, while the quantitative analysis was used on the quality of the images. Finally, the best analysis in accuracy specification used in UAV processing method will be determined.